2014
DOI: 10.3390/ijms150813406
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Lead on the Morphology and Structure of the Nucleolus in the Root Tip Meristematic Cells of Allium cepa L.

Abstract: To study the toxic mechanisms of lead (Pb) in plants, the effects of Pb on the morphology and structure of the nucleolus in root tip meristematic cells of Allium cepa var. agrogarum L. were investigated. Fluorescence labeling, silver-stained indirect immunofluorescent microscopy and western blotting were used. Fluorescence labeling showed that Pb ions were localized in the meristematic cells and the uptake and accumulation of Pb increased with treatment time. At low concentrations of Pb (1–10 μM) there were pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
15
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(17 citation statements)
references
References 58 publications
2
15
0
Order By: Relevance
“…Later, the 'Al-structure' phenomenon was confirmed by Liu & Jiang (1991) using the silver staining technique for the first time. After that, we found that besides Al, some heavy metals such as Cd, Pb, Cu, Ni, Co, Mg and Hg could also affect nucleoli and induce the phenomenon mentioned above in Allium cepa, A. sativum, Vicia faba and Zea mays (Liu et al 1995, Jiang & Liu 2000, Liu et al 2003, 2004, Qin et al 2013a, Jiang et al, 2014, but the amounts of extruded materials were less than in the Al treatment. The Cd-induced phenomena observed in this investigation were that some tiny particles containing argyrophilic proteins were scattered in the nucleus of root tip cells and leached out from the nucleus to the cytoplasm (Figure 2).…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Later, the 'Al-structure' phenomenon was confirmed by Liu & Jiang (1991) using the silver staining technique for the first time. After that, we found that besides Al, some heavy metals such as Cd, Pb, Cu, Ni, Co, Mg and Hg could also affect nucleoli and induce the phenomenon mentioned above in Allium cepa, A. sativum, Vicia faba and Zea mays (Liu et al 1995, Jiang & Liu 2000, Liu et al 2003, 2004, Qin et al 2013a, Jiang et al, 2014, but the amounts of extruded materials were less than in the Al treatment. The Cd-induced phenomena observed in this investigation were that some tiny particles containing argyrophilic proteins were scattered in the nucleus of root tip cells and leached out from the nucleus to the cytoplasm (Figure 2).…”
Section: Discussionmentioning
confidence: 93%
“…The evidence from indirect immunofluorescent microscopy demonstrate that fibrillarin and nucleolin are also migrated from the nucleoli to the nucleoplasm or to cytoplasm in the root tip cells of Allium cepa and Hordeum vulgare under Al, Pb and Cu stress, which is consistent with the phenomena obtained from silver staining method. (Qin et al 2013b, Jiang et al 2014, Wang et al 2015. Data here revealed that the two NPs were localized in nucleoli in the untreated root tips of H. vulgare.…”
Section: Discussionmentioning
confidence: 99%
“…Pb has no metabolic role in the growth of plants (Herbette et al 2006); however, various adverse effects, such as the inhibition of seed germination, chlorosis, and stunted plant growth, have been reported in Pb-stressed plants (Ghelich et al 2014;Jiang et al 2014). Adverse effects were also detected at the molecular level (Ghelich et al 2014;Jiang et al 2014;Malar et al 2014;Wang et al 2013) where they caused the homeostasis of the inner and outer environments of a cell to be broken, leading to cellular dysfunction (Sharma et al 2014;Xu et al 2014). Even a small amount of Pb can be toxic or lethal to plants (Islam et al 2008;Shu et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Heavy metals also affect plant development either by depositing on the surfaces of plants or by entering the plant cells (Ernst et al 1983;Jordao et al 2006). Heavy metal contaminants arise mainly from anthropogenic activities, such as the unsystematic use of pesticides, discharge of untreated industrial wastes and effluents, illegal solid waste disposal and dumping, high burning rate of fossil fuels, and mining (Jiang et al 2014;Salt et al 1995;Shen et al 2013;Wang et al 2013). Lead (Pb) is a toxic metal that is stably persistent in soil and is easily taken up by plants but is hard to degrade (Chen et al 2000;Kanwal et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Lead toxicity to plants has been widely investigated (Jiang et al, 2014;Cha-Um et al, 2009;Sharma et al, 2005). Pb is not an essential element for plants, but it can be absorbed by the roots of crop and transported to shoots, and enter the food chain.…”
Section: Introductionmentioning
confidence: 99%